Phenomenology Of The Minimal Supersymmetric Standard Model Without R–Parity - O'Leary, Benjamin Hugh (My University, 2007)
This thesis is an investigation into the current bounds on the trilinear R–parity–violating couplings in the Minimal Supersymmetric Standard Model without R–parity conservation. The model is described, and its implications are discussed. Bounds on the couplings are obtained from leptonic and mesonic decay data, approximating mediating sfermions as much heavier than the decaying particles and assuming that only one set of couplings is non–zero for each decay. Those bounds from the purely leptonic decay data are compared to bounds from the LEP–II data, over a large range of sfermion masses. A potential signal of R–parity–violation at existing lepton colliders is calculated assuming that certain couplings are close to their bounds. The signal is found to be feasible and the backgrounds to the process are found to be negligible.
Keywords: Particle Physics Theory; Physics